The Plantitas and Their Plants Gardening in Time of the Pandemic: A Case of Sitio Lasang Planters in Koronadal City, Philippines - Zahara A. Alamada; Diana Jean T. Cuevas; Julie Bee D. Tolin; Adonis Besa (Indonesian Journal of Multidiciplinary Research, 2022)
The purpose of the study is to find out the lived experiences of seven purposively chosen plants (planters) on plants gardening in time of the pandemic. The study was conducted in Sitio Lasang, Koronadal City. On the participants’ involvement in plants gardening in times of pandemic, it was found out that because of the lockdown, they make themselves busy by involving in plant gardening. On how they develop their gardens, the participants revealed that they propagate plants from their collections, being purchased, and through barter. On why they chose plants’ gardening in time of the pandemic, the participants revealed that they chose to plant because of leisure time and the safety and security of the family against the pandemic. In terms of benefits of plant gardening amidst pandemic to the plants, it is found out that plants’ gardening aside from economic support, serves them as a stress reliever. Furthermore, on the effects of plants’ gardening, it was found out that gardening serves as a workout and alternative means of doing something good while in the home.